Genome-Wide Identification and Comparative Analysis of the ASR Gene Family in the Rosaceae and Expression Analysis of PbrASRs During Fruit Development - Zhao, Biying; Yi, Xianrong; Qiao, Xin; Tang, Yan; Xu, Zhimei; Liu, Shanting; Zhang, Shaoling (Frontiers in Genetics, 2021)
The members of the Abscisic Acid (ABA) Stress and Ripening gene family (ASR) encode a class of plant-specific proteins with ABA/WDS domains that play important roles in fruit ripening, abiotic stress tolerance and biotic stress resistance in plants. The ASR gene family has been widely investigated in the monocotyledons and dicotyledons. Although the genome sequence is already available for eight fruit species of the Rosaceae, there is far less information about the evolutionary characteristics and the function of the ASR genes in the Rosaceae than in other plant families. Twenty-seven ASR genes were identified from species in the Rosaceae and divided into four subfamilies (I, II, III, and IV) on the basis of structural characteristics and phylogenetic analysis. Purifying selection was the primary force for ASR family gene evolution in eight Rosaceae species. qPCR experiments showed that the expression pattern of PbrASR genes from Pyrus bretschneideri was organ-specific, being mainly expressed in flower, fruit, leaf, and root. During fruit development, the mRNA abundance levels of different PbrASR genes were either down- or up-regulated, and were also induced by exogenous ABA. Furthermore, subcellular localization results showed that PbrASR proteins were mainly located in the nucleus and cytoplasm. These results provide a theoretical foundation for investigation of the evolution, expression, and functions of the ASR gene family in commercial fruit species of the Rosaceae family.